Towards a theoretical model for LSP lexicography in Ndebele with special reference to a dictionary of linguistic and literary terms - Nkomo, Dion (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Afrikaans and Dutch))—Stellenbosch University, 2008.